The connectors : how the world's most successful businesspeople build relationships and win clients for life - Kuzmeski, Maribeth (Hoboken, N.J. : Wiley, 2009)
Learn the relationship-building secrets that lead to lifelong clients, repeat customers, and endless referralsIn today's commoditized marketplace, no matter what product or service you sell, there's probably someone somewhere able to offer it cheaper, faster, and maybe even better. So how do you differentiate yourself from your competitors? The Connectors shows that the only thing that truly sets you apart is the quality of your relationships with your clients and customers. Everyone knows that relationships are important in business. Yet most people would admit that their relationships could b.
The common denominator of greatness and success : it's not money, it's people! -- You can be a connector even if you're not a natural people person : how social intelligence makes a major difference in business -- The connector IQ assessment : am I socially intelligent? -- The red zone connectors formula : the principles for building valuable relationships -- Develop a true "what's in it for them" mentality : focusing on others brings more for you -- Listen! Curiously listen! -- Important questions to ask that attract connections -- Getting the sale to close itself : using creative strategies to sell without selling -- Create a memorable experience : differentiating yourself by the impact you leave on others -- Gain a stream of profitable referrals : the litmus test for relationship success -- The employee connection : the critical factor in creating clients for life -- I don't have time to connect! Finding the time to connect with an already busy schedule -- Find a mentor : the influence that leads, motivates and holds you accountable -- Women's organizations : fulfilling a unique need for women to connect -- How to get the most from Outlook, ACT, and other CRM software : strategies for organizing and tracking relationships -- Christmas cards don't work : meaningful strategies for keeping in touch -- Using speaking skills to develop relationships : simple strategies to connect powerfully when speaking to small and large groups -- Connecting through social media technology : how to get the most out of Facebook, LinkedIn, and other social networking sites -- The contrarian networking strategy : create truly effective networking not focused on networking -- Coaching your way through to better relationships : a self-coaching exercise for improving business relationships -- Financial advisor relationship strategies : a niche-based look at connecting with dramatic sales results.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Relationship marketing; Business communication; Marketing relationnel; Communication dans l'entreprise.; BUSINESS & ECONOMICS -- Motivational; BUSINESS & ECONOMICS -- Mentoring & Coaching; Business communication; Relationship marketing